The formation of conflict logical readiness of the future teachers-psychologists - Elena Kharlanova, Asem Bissembayeva, Nadezhda Sivrikova, Swetlana Roslyakova,; Valentina Zherebkina, Nadezhda Sokolova, Elena Moiseeva, (Opción, 2019)
The purpose of the research was to develop and implement the models of conflict logical competence formation among the future teachers-psychologists. The pedagogical experiment with pre- and post-test demonstrated the growth in the formation degree of conflict logical readiness of the teachers-psychologists in experimental groups that the model of conflict logical readiness formation was realized in. During the research it was found that the application of the offered technique led to the growth in the number of students possessing a high level of knowledge and skills in conflict resolution, the ability to manage their emotions and professionally important personal qualities.